Essays on current account dynamics and fiscal rules in sub-Saharan Africa - Ayot, Kenrick Otieno (School of Economics, 2021)
Large and persistent current account and fiscal deficits coexisting alongside high public debt levels pose significant risks to macroeconomic stability and limit policymaking options. This thesis focuses on the current account dynamics and fiscal policy in the sub-Saharan Africa region. Over the past two decades, countries in this region have experienced large and persistent current account and fiscal deficits as well as a recent upsurge in public debt. In response to this situation, these countries are beginning to adopt fiscal rules whose primary objective is to rein in discretionary fiscal policy. This thesis examines the attendant issues within a broad context of three interrelated empirical studies, presented in separate chapters. The first study (chapter two) examines the overall sustainability of current account balances in sub-Saharan Africa and evaluates the pattern of current account adjustment in the region. The common approach for testing current account sustainability involves testing the violation of the intertemporal budget constraint. This was implemented by testing for a cointegrating relationship between exports and imports plus net interest payments on external debt using a panel error correction model. Based on a sample of 35 sub-Saharan Africa countries from 1980-2017, the study found evidence that current account balances are weakly sustainable in the region. In addition, countries in the region face a gradual current account adjustment pattern. On average, it takes six years for the current account to return to its long-run equilibrium after a disturbance, exposing these countries to prolonged spells of current account deficits and rising debt levels when corrective measures are not put in place. The second study (chapter three) examines the twin deficit hypothesis, or the effect of fiscal deficit on the current account deficit, and how the level of public debt impacts this relationship. Empirical studies that test this hypothesis often arrive at mixed results, possibly due to the omission of debt threshold effects on the current account. Thus, debt thresholds were included in the model used in this chapter. Using 2000-2016 data from 33 sub-Saharan Africa countries, a linear dynamic panel data model was estimated to address the twin deficit question. Next, a dynamic panel data threshold model was estimated to investigate how different debt regimes affect the twin deficit relationship. The empirical results for the linear model show that the fiscal deficit worsens the current account―thus the twin deficit hypothesis holds. However, introducing a debt threshold into this model resulted in different outcome. Based on an endogenously determined threshold level of debt, xiii which splits the sample into low and high debt regimes, the results reveal that the fiscal deficit continues to worsen the current account in the lower debt regime, whereas in the higher debt regime the pattern changes and the fiscal deficit loses its effect on the current account. These findings point to the uncertain effects of fiscal policy on the external imbalance when public debt reaches high levels. The third study (chapter four) examines the overall impact of fiscal rules on fiscal performance in the sub-Saharan Africa region. In addition, it evaluates whether there are any differences in fiscal performance between countries with and without the fiscal rules. The study used the fiscal balance as a measure of fiscal performance, while a time varying composite fiscal rule index was used to capture the effects of fiscal rules. The fiscal rule index was based on the updated IMF's fiscal rules dataset. Baseline regression examined the effect of fiscal rules on fiscal performance and a fiscal policy reaction function was estimated on 1997-2015 data from 24 sub-Saharan Africa countries that implemented these rules. The regression results suggest that fiscal rules improve fiscal performance. In particular, the fiscal rules for the budget balance, debt and revenue, are found to have positive and significant effects on fiscal performance. The same regression was repeated based on supranational rules. The results reveal that supranational rules are more effective compared to national rules. The second part of the empirical analysis compared the fiscal performance between these 24 countries that have fiscal rules and 16 countries that do not implement the rules. The time period was also expanded to include 1980-1996, prior to adoption of fiscal rules. A difference in differences model was then estimated using the treatment effect method. The results reveal that there is a significant improvement in fiscal performance for countries which have fiscal rules compared to those without fiscal rules. The main conclusion from this exercise is that fiscal rules have been effective in instilling fiscal discipline in the region; therefore, there is significant benefit for countries to adopt fiscal rules. This research supports the view that there is a causal relation between the fiscal deficit and the current account balance in most sub-Saharan Africa countries. The nature of this dynamic relationship appears to depend largely on the level of public debt. Thus, fiscal rules present an effective instrument to influence the fiscal deficit and therefore the current account balance.